Nanostructured materials : processing, properties and potential applications - Koch, C. C. (Materials science and process technology series. Electronic materials and process technology., 2002)
Nanostructured materials include atomic clusters, layered (lamellar) films, filamentary structures, and bulk nanostructured materials.